Synthesis and Surface Properties of Polyether‐Based Silicone Surfactants with Different Siloxane Groups. Issue 4 (18th March 2019) - Tan, Jinglin; He, Ziyan; Miao, Yongxiang; Lin, Miaomiao
Abstract: A series of polyether‐based silicone surfactants with different hydrophobic chains (trimethylsiloxy, triethylsiloxy, and triisopropylsiloxy) were synthesized. The molecular structures were confirmed using 1 H nuclear magnetic resonance (NMR), 13 C NMR, 29 Si NMR, and fourier transform infrared spectroscopy (FT‐IR). The effect of the siloxane groups on the physicochemical properties, surface tension ( γ ), critical micelle concentration (CMC), surface tension at the CMC ( γ CMC ), adsorption efficiency ( p C20 ), surface pressure at the CMC ( π CMC ), maximum surface excess (Γmax ), single silicone surfactant molecule at the air/water interface ( A min ), and the standard free energy of adsorption ( Δ G ads 0 ), of the polyether‐based silicone surfactants was investigated. Results indicate that the polyether‐based silicone surfactants can reduce the surface tension of water to approximately 25–31 mN m −1 and the surface activity of silicone surfactants is enhanced with increasing branched trimethylsiloxyl and sterically hindered siloxane groups.